Evaluation of in vitro longevity of caprine cauda epididymal sperms at different storage intervals of time - SWAIN, DILIP KUMAR; SWARNKAR, PRASANT; KUMAR, JITENDER; YADAV, SARVAJEET (The Indian Journal of Animal Sciences, 2012)
The present study was designed to evaluate the effect of both temperature and storage time interval on the cauda epididymal sperm quality in bucks. The testes collected in normal saline at 4°C were exhibited improved sperm attributes at all periods of storage temperature as compared to the testes collected in normal saline at room temperature as well as preserved at the same temperature. In both cases, with the passage of time of storage the sperm features started deteriorating. That is why the study recommended that to maintain the sperm attributes for a longer period of storage, suitable antioxidants and amino acids may be supplemented. The sperms should be isolated as soon as possible after the collection of the testes to maintain the integrity and quality of the sperm from the cauda. It was evident that, as soon as possible, the sperms from the cauda should be recovered as well as storage temperature should be lesser than 4°C. Suitable strategies should be developed to cryopreserve the cauda epididymal sperms.